Kajian Kualitas Air berdasarkan Keanekaragaman Plankton di Muara Sungai Donan - Mahardika Nur Permatasari; Jefri Anjaini; Hery Irawan; Philipus Uli Basa Hutabarat (Jurusan Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Timor, 2024)
The Donan River estuary is the area where the Donan River meets the Nusakambangan Strait, has a level of pollution that shows an increase, one of which is caused by human activity. Phytoplankton has an important role in determining the status of waters by knowing the diversity and types of plankton. The research aims to determine the community structure of the phytoplankton as a biological indicator and determine the condition of the Donan River Estuary based on the Diversity Index. This research was conducted out in April-May 2024. The sampling method was a sample survey. The results of this research show that the phytoplankton abundance of the Donan River estuary ranges from 42-382 ind/L, which means it is oligotrophic. The results of phytoplankton identification showed that many Bacillariophyceae and Cyanophyceae classes were found. The diversity index value at station 1 is 1.199 and at station 2 is 1.623. The diversity index value shows that the Donan River Estuary has moderate phytoplankton community stability and water quality is moderately polluted. Based on the uniformity index at station 2 the uniformity is more even and based on the dominance index there is no dominant genus.